The Effect of Greeting Card Media on Students’ Writing Skill - Septiani, Irefi; Wagiyo, Supiah; Juriana, Juriana (English Education Department, 2023)
The research was aimed to know about the effect of greeting card media on students’ ability in writing of eighth grade at junior high school in Bangka Belitung. This experimental study employed quasi experimental design. The samples used was the 8th grade students of high school many as 54 students. The research used a writing test as a data collection technique. In the technique of analyzing the data, the research used t-test was in the form of paired sample t-test to test the hypothesis through the SPSS. The finding showed an improvement in students' writing when they used greeting card media. The result of t-obtained 5.712 was greater than the t-table 2.007. The result of 2-tailed significance 0,00 have less score than 0,05. Thus, it menas that the experimental group had a greater performance than the control group.